48 The nature of complex need in specialist palliative care referrals. (13th October 2019) - Swenson, Connie; MacArtney, John; Perry, Rachel; Hetherington, Lucy; Graham-Wisener, Lisa; Lamberton, Hazel; Carduff, Emma; Murray, Scott; Finucane, Anne
Abstract : Background: Understanding complex need as the defining characteristic of episodes requiring specialist palliative care (SPC) is key to hospice service development. A single definition of complex need is lacking, however markers of complex need include: presence of multiple needs, needs across different domains, interactions between different needs and fluctuating needs. We examined which markers of complex need are present in referrals to a hospice service. Methods: Mixed-method service evaluation consisting of a case-note review and staff focus groups. Results: Physical needs were most frequently described in referral documents (91%) though needs were present across all domains. Markers of complexity across more than one domain were present in 95% of referrals. Psychological, social or spiritual needs were described in 68% of referrals; fluctuating needs in 67%; carer needs were documented in 52%. Referral forms were viewed as limited for capturing complexity. The quality of a referral was perceived as influenced by the experience and confidence of the referrer, their knowledge of the services available, the resources available to the referrer to meet the patients needs and the patient's diagnosis. Conclusions: Complex needs were documented in most referrals to hospice services. However, clarity on what service was being sought to meet a person's needs was lacking. There is scope for hospices to improve referral quality by defining what services are offered to meet which needs; communicating regularly with referrers, and providing education or training to support referrers to improve their ability to meet patient needs directly.